Financial integration and macrofinancial linkages in Asia crises, responses, and policy considerations. - Asian Development Bank.; Joint author;Editor. ([Manila] Asian Development Bank, 2020)
This report reviews evidence of the macrofinancial linkages and feedback effects of financial distress in Asia. It proposes policy considerations and coordinated responses to enhance financial stability and resilience. The Asian financial landscape has become more interconnected over the past 2 decades. Previous financial crises have proven how volatility can transmit rapidly across an interconnected financial network. Moreover, empirical analyses have shown how it can reverberate across the macroeconomy. With a summary of lessons from past financial crises, this report also analyzes the impact of deeper financial integration on economic vulnerability.
Keywords: Finance -- Asia; Financial crises -- Asia; Electronic books